Relationships of Insulin Action to Age, Gender, Body Mass Index, and Waist Circumference Present Diversely in Different Glycemic Statuses among Chinese Population - Shao-jie Pang; Qing-Qing Man; Shuang Song; Peng-Kun Song; Zhen Liu; Yu-Qian Li; Shan-Shan Jia; Jing-Zhong Wang; Wen-Hua Zhao; Jian Zhang (Journal of Diabetes Research)
Introduction. To study the influence of different glycemic statuses on the relationship of insulin action to age, gender, body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) among Chinese population. Methods. A total of 35,327 participants (17,456 males and 17,871 females) were included in this nationally representative cross-sectional study. Glycemic status was defined according to the 2010 American Diabetes Association criteria. Fasting insulin was measured by the chemiluminescence method. Results. Insulin and HOMA-IR levels were the highest in newly diagnosed diabetes and were lowest in normal fasting glucose (NFG) (P<0.001). Insulin and HOMA-IR levels were higher in females (P<0.001) than in males with previously diagnosed diabetes and impaired fasting glucose (IFG) and NFG, meanwhile decreased with age (P<0.001) among IFG and NFG participants. As compared with participants with a BMI from 18.5 to 19.9, those in the lowest BMI category (<18.5) had a significantly elevated risk of IR (OR, 1.96; 95% CI, 1.01–3.80), as did those in the higher BMI categories among NFG participants. The risk of IR increased with WC and WHtR, and the response was linear (P<0.001 for linear trend) for the participants with NFG but not in those with IFG. Conclusions. Different glycemic statuses significantly affect the relationships of insulin action to age, gender, BMI, WC, and WHtR among Chinese population.